Brilliant crystallisation in the anterior chamber and subretinal space following adjunctive intravitreal ranibizumab for diabetic vitrectomy. (23rd October 2012) - Bastion, Mae-Lynn Catherine; Mustapha, Mushawiahti; Ho, Ivan
Abstract : To report a unique case of crystallisation in the anterior chamber and subretinal space in a Malay lady following inadvertent subretinal injection of ranibizumab prior to vitrectomy for proliferative diabetic retinopathy.